Ferromagnetic relaxation in (1) metallic thin films and (2) bulk ferrites and composite materials for information storage device and microwave applications - Kalarickal, Sangita S., author; Patton, Carl E., advisor; Bradley, R. M., committee member; Liesure, R. G., committee member; Menoni, C. S., committee member; Camley, R. E., committee member (Colorado State University. Libraries, 2006)
For a better understanding of fundamental magnetic loss processes in materials needed for microwave and information storage device applications, the ferromagnetic resonance (FMR) linewidth has been studied in (1) ferromagnetic metal films, (2) bulk ferrites, and (3) ferrite-ferroelectric composites. These materials have wide applications for high density magnetic storage as well as microwave isolators and circulators. The field of microwave magnetics, especially for magnetic metals, is ruled by a set of purely phenomenological models for the damping of the magnetodynamics. These operational models are supplemented by models for actual physical loss mechanisms. All of these models, phenomenological and physical, yield specific predictions of the linewidth vs. frequency response. Data on the frequency dependence of the ferromagnetic resonance linewidth can provide (1) insight into the relevant microwave loss processes and (2) a guide for the proper application of the different phenomenological models to materials design and device development. Comprehensive linewidth data also allow for (1) the identification of truly intrinsic losses and (2) the clarification of extrinsic losses due to inhomogeneities, imperfections, etc., that are candidates for elimination through the development of better materials. The frequency dependence of the FMR linewidth in Permalloy films shows that the dominant loss mechanism is akin to a Landau-Lifshitz or Gilbert type of phenomenological damping model. This trend matches the physical process of magnon-electron scattering. The frequency dependence of the Permalloy film FM R linewidth can be modeled by a com bination of Landau-Lifshitz/Gilbert damping and broadening due to ripple fields and inhomogeneities. In Fe-Ti-N thin films, there are large extrinsic contributions that relate to two magnon scattering. This appears to be connected with changes in crystal structure due to the addition of nitrogen to the Fe-Ti matrix. The frequency dependence of the linewidth in hot isostatic pressed polycrystalline yttrium iron garnet explicitly demonstrates the anisotropy based two magnon scattering process for the randomly oriented grains. Microwave loss data for nickel zinc/barium strontium titanate composite materials show that composite or multifunctional materials can play a useful role in future systems that require electric field tuning and low power budgets.
Keywords: condensation; electromagnetism; electromagnetics; condensed matter physics